Local Structure Analysis around Ti in Lead Zirconate Titanate by X‐Ray Fluorescence Holography. Issue 11 (20th July 2020) - Hayashi, Kouichi; Lu, Cong; Ang, Artoni Kevin R.; Ohwada, Kenji; Xie, Yujuan; Hu, Wen; Matsushita, Tomohiro; Happo, Naohisa; Hosokawa, Shinya; Bokov, Alexei A.; Ye, Zuo-Guang
Abstract : To clarify the mechanism of ferroelectricity in lead zirconate titanate (PZT), the local structure around Ti in a Pb(Zr0.7 Ti0.3 )O3 single crystal is investigated using X‐ray fluorescence holography. The raw hologram data are contaminated by periodic noise due to the fluctuation of the incident X‐ray intensity. The periodical noise is successfully removed using an inverse Fourier transformation method. From the filtered holograms, the atomic images around Ti can be reconstructed clearly. The reconstructions of B‐site cations demonstrate an outward displacement of the neighboring Ti from the ideal B‐site position, indicating an expansion of the local lattice around Ti. In addition, the splitting of Pb images is found, and the relative displacement between Ti and Pb atoms is deduced. These results contribute to the understanding of the local structure of PZT and can reveal the microscopic origins of very high dielectric and piezoelectric responses, which are essential for designing new and improved ferroelectric materials. Abstract : The local structure around Ti in a lead zirconate titanate (PZT) is visualized using X‐ray fluorescence holography. An expansion of the local lattice around Ti and displacements between Ti and Pb atoms are observed. These results can contribute in understanding the local structure in PZT and can help reveal the microscopic origins of its piezoelectric response.